Standardization of irrigation requirement of salad cucumber in polyhouse - DEEPA C.N JOSENA JOSE SREEMOL S; Dr. E.K Mathew (Guide) (Tavanur 2010 Kelappaji College Agricultural Engineering and Technology)
Standardization of irrigation requirement of salad cucumber in polyhouse
Standardization of irrigation requirement of salad cucumber in polyhouse